Internacionalização do capital no setor sucroenergético do Triângulo Mineiro/Alto Paranaíba: estratégias políticas e territoriais - Campos, Natália Lorena (2019)
The mesoregion of the Triângulo Mineiro/Alto Paranaíba has become an important space for brazilian sugarcane industry and of hegemonic capitals. The globalization was a determinant factor for these financial investment inputs. The agrobusiness gained strength in the region of Triângulo Mineiro, primarily with soybean production and currently with sugarcane cultivation, owing to the agriculture modernization and policies aiming agricultural frontiers expansion of the Cerrado areas. Triângulo Mineiro currently concentrates 60% of the plants in the state of Minas Gerais that are controlled by Northeast, South Central region, and foreign groups. The beginning of the foreign investments inputs into the sugarcane industry occurred during the early 2000s. This period was marked by mergers and acquisitions of Brazilian and multinational companies, which associated the Brazilian territory with agrofuels production. The process of fusion and acquisition of Brazilian and multinational companies intensified after the financial crisis of 2008. The period of crisis facilitated the foreign investments inputs with support of Brazilian government aiding in sector financialization. Thus, the objective of the present study is to understand the new capital configurations in sugarcane activities based on the internationalization of this sector in the region, as well as the intentions of external capital and its political and territorial strategies. The mesoregion has five plants controlled by foreign groups - Bunge (United States/Netherlands), British Petroleum (UK), and Dow-chemical (United States), and these groups are involved in our analysis. Methodologically, this study was constructed through interpretations that involve the theme, mainly regional ones, data analysis that allowed to understand the territorialization of the sugarcane industry, and field research focused on internationalization, focusing on the foreign groups present in the region. Based on reflections that determined the current configuration of the Minas Gerais sugarcane industry, our intention was to demonstrate the corporate use of the territory and its appropriation by the transnational companies, and the interest in the production of agricultural commodities. Among the main conclusions of the thesis, we must consider that there is an increase in interest in the global production of new energy sources. Sugar cane is a flexible condition since it is used for producing food and energy, and this has attracted foreign investments and generated a series of effects in the Brazilian countryside. The process of capital internationalization and sugarcane production has a rebound on regional structures, such as increased production of agricultural commodities to the detriment of food production, as well as peasant expropriation and the precariousness of rural workers. In addition, the acquisition of land by foreigners reflects in a greater exploitation of the lands and resources by these agents that begin to control the sugarcane production in the internationalized spaces. Therefore, we observed a consolidation of the Triângulo Mineiro/Alto Paranaíba mesoregion in the production of agrofuels, becoming a competitive region and associated with external capital, interested in exploiting comparative and competitive advantages of sugarcane production in new frontiers.